The effect of carbohydrate restriction on prostate cancer tumor growth in a castrate mouse xenograft model. Issue 5 (4th October 2012) - Caso, Jorge; Masko, Elizabeth M.; II, Jean A. Thomas; Poulton, Susan H.; Dewhirst, Mark; Pizzo, Salvatore V.; Freedland, Stephen J.
Abstract BACKGROUND No‐ and low‐carbohydrate diets delay tumor growth compared to western diet (WD) in prostate cancer (PCa) xenograft studies. The effect of these diets in concert with androgen deprivation is unknown. METHODS A total of 160 male SCID mice were injected with 1× 105 LAPC‐4 human PCa cells. Of these, 150 mice were castrated and randomized to an ad libitum WD or fed via a paired‐feeding protocol with a no‐carbohydrate ketogenic diet (NCKD), 10% carbohydrate diet, or 20% carbohydrate diet. The remaining 10 mice were not castrated and were fed an ad libitum WD. The mice were sacrificed once volumes reached 1, 000 mm3 and survival tested using the log‐rank test. Serum from the median surviving 8 mice/group was assayed for insulin, IGF‐1, and IGFBP‐3. RESULTS Body weights were roughly equal among groups. The 10 non‐castrated mice experienced accelerated tumor growth. Among castrated mice, WD had the most rapid tumor growth; 20% carbohydrate diet the slowest (P = 0.046). Survival was not significantly different among the various carbohydrate restricted groups (P = 0.51). When pooled, there was a non‐significant trend (P = 0.11) in improved survival among the carbohydrate restricted diets versus WD. No significant difference in serum insulin, IGF‐1, and IGFBP‐3 levels was noted among all groups at pre‐randomization or at sacrifice. CONCLUSIONS A 20% carbohydrate diet slowed tumor growth versus a WD. Though the benefit of carbohydrate restriction was somewhat less than in prior studies in non‐castrate mice, these data still suggest diets achievable in humans may play a role in PCa management. Prostate 73: 449–454, 2013. © 2012 Wiley Periodicals, Inc.